Recent policy trends and developments related to the conservation, use and development of genetic resources - Bragdon, S.; Downes, D. (1998)
The erosion of genetic resources and hence diversity continues at an alarming pace. Simultaneously, technologies which develop and make use of these resources outpace the ability of laws and societies to understand and cope with them. Spurred by technological advances, appreciation of the monetary and non-monetary value of genetic resources has grown, leading to increasing conflict over rights and responsibilities for these resources. Developments in international and national law and policy over the past 5 years have significantly changed the policy environment relating to the management and control of genetic resources. Decision-makers trying to devise good, coherent, consistent policy on genetic resources are faced with a myriad of related, rapidly evolving issues being discussed in multiple national and intergovernmental fora. The task of discerning all the issues of relevance to the conservation and management of genetic resources and then integrating them into consistent policy is extremely complex. With continuing globalization and increased understanding of the world's interdependence on all levels, few important issues can be meaningfully addressed without undertaking the complex process of unweaving and understanding relevant issues and then integrating a policy response. Better analytical tools are needed to enable policy-makers to evaluate the trade-offs and consequences of particular decision. Analysis of recent development need in terms of their objectives, interests and relations to one another is a necessary first step in developing better analytical tools for policy-makers. This paper analyzes developments in the past 5 years, identifying cross-cutting issues and trends that have emerged including farmers' rights and interests of indigenous and local communities, benefit-sharing, access to genetic resources, patenting and industry trends, and sui generis protection of plant varieties. The time is ripe for an evaluation of where we have been and where we want to go with regard to the conservation, use and development of genetic resources. The paper identifies and analyzes key decision points and critical, emerging legal and policy issues having an impact on genetic resources. It thereby provides the foundation for beginning to assess decision, where they are leading relative to policy objectives and whether or not course corrections are warranted.